2016
DOI: 10.1007/s12469-016-0144-9
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the impact of metro rail stations on residential property values: evidence from Tehran

Abstract: Building a rail transit system into a neighbourhood generally raises expectations about the positive impact of the rail project on property values. Despite this general belief, the paper argues that the nature and magnitude of the effect vary depending on local and regional contextual factors. In this respect, the introduction of Tehran's Metro Rail System (TMRS) between the low-income/run-down neighbourhoods on the south side and high-quality/affluent neighbourhoods on the north side of the city provides a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 25 publications
0
17
0
3
Order By: Relevance
“…The authors found that an overall negative effect of the metro stations on the sales value of residential properties located in Tehran's affluent neighborhoods. On the contrary, the effect is positive and high for properties located close to the southern stations in the poor and run-down neighborhoods of the city [4]. show that the coefficient of the distance to the nearest subway station is The coefficient reaches −0.247471; of which the absolute value is higher than the absolute value of the coefficient of the distance to the nearest subway station in the regression of the entire subway line 3 which is −0.099011.In the center area, the influence coefficient of the distance to the nearest subway line 3 stations is −0.079166.…”
Section: Literature Reviewmentioning
confidence: 87%
“…The authors found that an overall negative effect of the metro stations on the sales value of residential properties located in Tehran's affluent neighborhoods. On the contrary, the effect is positive and high for properties located close to the southern stations in the poor and run-down neighborhoods of the city [4]. show that the coefficient of the distance to the nearest subway station is The coefficient reaches −0.247471; of which the absolute value is higher than the absolute value of the coefficient of the distance to the nearest subway station in the regression of the entire subway line 3 which is −0.099011.In the center area, the influence coefficient of the distance to the nearest subway line 3 stations is −0.079166.…”
Section: Literature Reviewmentioning
confidence: 87%
“…No obstante, esto debe ser un tema de profundo debate y transformación de instrumentos de evaluación, ya que la literatura demuestra que en la mayor parte de los proyectos de transporte público en los que se ha analizado la variación de los valores inmobiliarios, ha existido un incremento (Cervero y Dai, 2014;Smith y Gihring, 2006;Suzuki et al, 2014;Wang, Potoglou, Orford y Gong, 2015); siendo pocos los casos en los que se han detectado decrementos o ningún cambio (Cohen y Brown, 2017;Devaux, Dubé y Apparicio, 2017;Forouhar, 2016). En la región latinoamericana, si bien existe poca exploración, se evidencia una tendencia similar: principalmente incrementos (Agostini y Palmucci, 2008;Mendieta et al, 2007;Munoz-Raskin, 2010;Rodríguez et al, 2010) y en raras ocasiones, efectos variables o ningún efecto (Bocarejo, Portilla y Pérez, 2013;Rodriguez, Vergel y Camargo, 2016).…”
Section: Evaluación De Impacto En Proyectos De Transporteunclassified
“…No obstante, esto debe ser un tema de profundo debate y transformación de instrumentos de evaluación, ya que la literatura demuestra que en la mayor parte de los proyectos de transporte público en los que se ha analizado la variación de los valores inmobiliarios, ha existido un incremento (Cervero y Dai, 2014;Smith y Gihring, 2006;Suzuki et al, 2014;Wang, Potoglou, Orford y Gong, 2015); siendo pocos los casos en los que se han detectado decrementos o ningún cambio (Cohen y Brown, 2017; Devaux, Dubé y Apparicio, 2017; Forouhar, 2016). En la región latinoamericana, si bien existe poca exploración, se evidencia una tendencia similar: principalmente incrementos (Agostini y Palmucci, 2008;Mendieta et al, 2007;Munoz-Raskin, 2010;Rodríguez et al, 2010) y en raras ocasiones, efectos variables o ningún efecto (Bocarejo, Portilla y Pérez, 2013;Rodriguez, Vergel y Camargo, 2016).…”
Section: Evaluación De Impacto En Proyectos De Transporteunclassified